Span Tables for Roof Purlins and Ceiling Joists in Some Social Forestry Species for Timber House Constructions - Punhani, R. K. (Indian Forester, 1995)
This paper contains tables of standard sizes of purlins and ceiling joists for housing in some Social Forestry species. This will serve as a ready reckoner for designing, construction and inspection of house construction in Social Forestry timbers. This will also help architects, builders and designers to use these tables withoust going in for detailed calculations.